2015
DOI: 10.3141/2496-05
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Utilization of Advanced Traveler Information by Active Seekers

Abstract: Intelligent transportation systems (ITS) have been deployed worldwide as a cost-effective means to mitigate concerns about congestion, safety, environment, and other issues. Researchers commonly use questionnaire surveys to gauge the public's response to the success of ITS deployments in achieving the stated ITS goal of improving customer satisfaction as well as the other goals of strengthening transportation safety, mobility, efficiency, productivity, energy, and environmental efforts. To differentiate itself… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, regarding the use of travel information sources, our findings are in consistent with these two studies. Other literature findings also showed that the availability and use of information technologies (Clark et al, 2015;Goulias et al, 2004), previous positive experience with travel information and a favorable attitude toward their usefulness (Farag and Lyons, 2010;Xu et al, 2010) play an important role in individuals' affinity to such technologies and the use of ATIS.…”
Section: The Relation Between Goal-frames Technophilia Community Trust Place Attachment and Individual Characteristicsmentioning
confidence: 93%
“…However, regarding the use of travel information sources, our findings are in consistent with these two studies. Other literature findings also showed that the availability and use of information technologies (Clark et al, 2015;Goulias et al, 2004), previous positive experience with travel information and a favorable attitude toward their usefulness (Farag and Lyons, 2010;Xu et al, 2010) play an important role in individuals' affinity to such technologies and the use of ATIS.…”
Section: The Relation Between Goal-frames Technophilia Community Trust Place Attachment and Individual Characteristicsmentioning
confidence: 93%